(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The research aims at establishing the role that cloud computing plays in the digital transformation of public services in Nigeria by focusing on its impact in terms of improving efficiency, accessibility, transparency, and innovation. The use of cloud computing technology has proved to be an indispensable means through which digital government can be enabled through data storage, information sharing, remote access to public services, and better collaboration between government institutions. Notwithstanding these benefits, there have been numerous challenges in the implementation of cloud computing in Nigeria's public institutions. The present research has employed the use of qualitative research methodology through a thorough review and analysis of related literature covering scholarly articles, government papers, policies, and reports on cloud computing and digital transformation within the Nigerian public sector. Qualitative analysis allows for the determination of major themes that cover areas such as cloud adoption, digital governance, cyber security, service delivery, and infrastructure among others. According to the results, cloud computing plays a role in the improvement of public services delivery through increased efficiency, reduced IT costs, better access to services, data integration, inter-agency cooperation, as well as transparency and accountability in government activities. Nonetheless, issues such as digital infrastructure inadequacy, cybersecurity risks, lack of skills, conflicting policies, budgeting, and data sovereignty remain challenges in the way of implementing cloud computing. This paper has demonstrated that cloud computing has enormous possibilities to facilitate the digitalization of government services in Nigeria and ensure better access by the citizens to effective and responsive government services. The study makes recommendations on the need to enhance the development of digital infrastructure, adopt sound cybersecurity policy frameworks, develop capacity of public service personnel, create harmonized policies, and develop collaborative relationship between government agencies and ICT providers.